Estimation of spatio-temporal variability in land surface temperature over the Ganga River Basin using MODIS data. Issue 13 (10th August 2022) - Mal, Suraj; Rani, Seema; Maharana, Pyarimohan
Abstract: The present study aims to estimate the trends in daytime land surface temperature (LST) and its relationship with other parameters such as elevation and land use/land cover (LULC) over the Ganga River Basin (GRB) during 2001–2019. The study examined monthly daytime clear-sky LST, elevation, LULC, snow cover area (SCA), clear-sky days, and aerosols data of the GRB. Annual mean clear-sky daytime LST has been declining at the rate −0.017 °C year −1 over the basin during the study period. At seasonal scale, LST has been rising during monsoon (average rate of 0.026 °C year −1 ), whereas other seasons show a decline with the highest magnitude during winter season (−0.078, o C year −1 ). The study observed pronounced warming trends (0.003 to 0.07 °C year −1 ) in post-monsoon above the elevation of 3000 m amsl indicating elevation-dependent warming (EDW) in the basin. The vagary in LST over the basin may be attributed to the changes in LULC, increasing aerosols loading, and rising hazy days.